Ticks parasitised feathered dinosaurs as revealed by Cretaceous amber assemblages - Peñalver, E; Arillo, A; Delclòs, X; Peris, D; Grimaldi, DA; Anderson, SR; Nascimbene, PC; la Fuente, R (Nature Publishing Group, 2017)
Ticks are currently among the most prevalent blood-feeding ectoparasites, but their feeding habits and hosts in deep time have long remained speculative. Here, we report direct and indirect evidence in 99 million-year-old Cretaceous amber showing that hard ticks and ticks of the extinct new family Deinocrotonidae fed on blood from feathered dinosaurs, non-avialan or avialan excluding crown-group birds. A †Cornupalpatum burmanicum hard tick is entangled in a pennaceous feather. Two deinocrotonids described as †Deinocroton draculi gen. et sp. nov. have specialised setae from dermestid beetle larvae (hastisetae) attached to their bodies, likely indicating cohabitation in a feathered dinosaur nest. A third conspecific specimen is blood-engorged, its anatomical features suggesting that deinocrotonids fed rapidly to engorgement and had multiple gonotrophic cycles. These findings provide insight into early tick evolution and ecology, and shed light on poorly known arthropod–vertebrate interactions and potential disease transmission during the Mesozoic.